2015
DOI: 10.1186/s13046-015-0185-y
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygote of TAP1 Codon637 decreases susceptibility to HPV infection but increases susceptibility to esophageal cancer among the Kazakh populations

Abstract: BackgroundThe role of human papillomavirus (HPV) may be involved in the development of esophageal cancer (EC) and the polymorphic immune response gene transporter associated with antigen processing (TAP) may be involved in HPV persistence and subsequent cancer carcinogenesis. The current study aims to provide association evidence for HPV with EC, to investigate TAP1 polymorphisms in EC and assess its association with HPV statuses and EC in Kazakhs.MethodsThe HPV genotypes in 361 patients with EC and 66 control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 57 publications
1
11
1
Order By: Relevance
“…HPV positivity was detected in 45.5 % of ESCC patients in this study, which is similar with previously reported data in Kazakhs [ 10 12 ], with a prevalence ranging from 30 % to 66.67 %. No correlation was observed between HPV positivity and clinicopathological characteristics, which is in agreement with previous studies on ESCC [ 51 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…HPV positivity was detected in 45.5 % of ESCC patients in this study, which is similar with previously reported data in Kazakhs [ 10 12 ], with a prevalence ranging from 30 % to 66.67 %. No correlation was observed between HPV positivity and clinicopathological characteristics, which is in agreement with previous studies on ESCC [ 51 ].…”
Section: Discussionsupporting
confidence: 92%
“…HPV DNA was detected as previously described [ 12 ]. Non-degenerate primer sets GP5+/6+ (forward: TTGGATCCTTTGTACTGTGGTAGATACTAC and reverse: TTGGATCCGAAAAATAAACTGTAAATCATATTC) amplifying a 150 bp fragment within L1 gene of a wide range of HPV types were used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies found that TAP1 polymorphisms could increase susceptibility to ESCC in the Kazakh population [ 35 ]. Moreover, TAP1, LMP2 and LMP7 are all located within a narrow region of the class II cluster of the major histocompatibility complex on chromosome 6 [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study reported an infection rate of 100%, which was confirmed by detection of the HPV16 E6 and E7 genes in a high-risk area in Anyang, Henan [ 37 ]. Some reports even found that HPV infection is an important factor contributing to the high incidence of ESCC in the Kazakh population in Xinjiang [ 35 ]. Indeed, a study on cervical cancer showed that the genetic makeup of host immune response genes may be responsible for biological variability to HPV infection [ 38 ].…”
Section: Discussionmentioning
confidence: 99%